Sustainability Science for Strong Sustainability - Dedeurwaerdere , Tom (Edward Elgar Publishing, 2014)
The dynamism of science has been catalytic for human prosperity in recent history. Conventional perspectives of the ivory tower model of modern science are, however, rivalled by the failure of humanity to tackle global crises of an economic, environmental and social nature. Operational solutions to these pressures have grown and exposed pitfalls of modern science to date. Sustainability Science for Strong Sustainability investigates core concepts, tools and institutional strategies of transdisciplinary sustainability science. Prominent research programs within heterodox economics, the environmental sciences and transition theory are explored through diverse case studies, revealing challenges and advancements for transdisciplinary research. In this book, the reform of modern science is facilitated by the consideration of action points to overcome the institutional barriers of putting sustainability science into practice. Researchers, students and policy practitioners will benefit from up to date knowledge on the practice of transdisciplinary research for sustainability